RANCANG BANGUN SISTEM INFORMASI PENGGAJIAN KARYAWAN MENGGUNAKAN METODE FUZZY TSUKAMOTO - Dicky Pradana Abdulrahman Julianto; Septi Andryana; Aris Gunaryati (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
Appreciation of employee performance is needed in a company to improve the quality of performance and enthusiasm for work for employees. One of them is PT. Olew Plasindo Jaya Makmur is engaged in cosmetic packaging distributors. This company gives appreciation in the form of bonuses to its employees. The calculation of the existing bonuses uses several criteria such as the employee's tenure and the employee's net salary. From the criteria obtained, it can be calculated using the Tsukamoto method, then creating decisions in the form of few and many variables. After the variable decision is obtained, it will produce a nominal employee bonus. The calculation of each variable is in an employee payroll information system called SIPEKA.